Pengaruh Penggunaan Media Sosial Instagram Terhadap Keputusan Pembelian Kaum Millenial Di Restoran Gokana Ramen & Teppan Mall Ratu Indah Makassar - Hany; Daniel Lallo Pakiding; Uli Urbanus Bubun; Westerini Lusdani (UKI Toraja Press, 2022)
Social media is an internet platform where it is possible for individuals to share directly and communicate continuously with their community. The use of social media has become part of the experience of growing up for teenagers to seek entertainment and the latest information. The purpose of this study is to analyze and examine the effect of using Instagram social media on millennial purchasing decisions at Gokana Ramen Restaurant & Teppan Mall Ratu Indah Makassar. The data collection technique was carried out with a quantitative approach with a sample size of 100 respondents. The data analysis method in this study used descriptive data analysis, simple linear regression analysis and hypothesis testing. The results of this study indicate that the use of Instagram social media has a significant and positive effect on millennial purchasing decisions at Gokana Ramen Restaurant & Teppan Mall Ratu Indah Makassar.